Literasi Pemanfaatan dan Pencegahan Efek Radiasi pada Masyarakat Lansia di Lingkungan Kecamatan Trawas Kabupaten Mojokerto - Aga Satria Nurrachman; Eha Renwi Astuti; Deny Saputra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Radiation can originate from various natural and artificial sources. Ionizing radiation can impact individual health because ionization events can result in DNA damage, cell death, and harm to tissues and organs. The elderly is one of the vulnerable groups that should receive more attention regarding their health conditions. Aging is a natural phase in the human life cycle that significantly affects various aspects of life, including health and quality of life. The quality of life in the elderly can be influenced by their well-being, emotions, physical health, occupation, cognitive abilities, and social life. In connection with the radiation phenomenon that can have serious implications for the health and quality of life of individuals, including the more vulnerable elderly population, adequate knowledge about safe radiation utilization and a detailed understanding of radiation's effects and prevention become essential in maintaining their health and improving their quality of life. Community outreach activities were conducted in the form of educational seminars with the aim of increasing the elderly community's literacy regarding the effects and utilization of radiation in the Trawas District, Mojokerto Regency, over a duration of one day. It is worth noting that the Trawas District, Mojokerto Regency, has experienced an increase in its elderly population over the past few years. The results of this community outreach program have shown a positive overall progress, with an increase in participants' self-confidence in understanding the provided material and an improvement in their knowledge regarding the utilization and prevention of radiation effects. This improvement is demonstrated by the significant difference between pre-test scores (mean value: 22.82) and post-test scores (mean value: 80.82), as assessed through a statistically significant paired T-test (t value: 35,537 with p<0.001) and Wilcoxon signed-rank test (p<0.001).